Properties of human blood monocytes. II. Monocytes from healthy adults are highly heterogeneous within and among individuals. Issue 2 (10th December 2013) - Hudig, Dorothy; Hunter, Kenneth W.; Diamond, W. John; Redelman, Doug
<x xml:space="preserve">Abstract</x> Background Human blood monocytes are known to include subsets defined by the expression of CD14 and CD16 but otherwise are often assumed to be relatively homogeneous. However, we had observed additional heterogeneity that led us to a more extensive examination of monocytes. Methods Blood samples from 200 healthy adults without known immunological abnormalities were examined by analysis with a hematology analyzer and by flow cytometry (FCM) to determine leukocyte differential counts, to identify subsets and to measure expression of monocyte‐associated molecules. Results The estimated cell counts of monocytes, neutrophils, total lymphocytes, and T cells all varied to a similar extent, that is, ±30–35%. The fractions of monocyte subsets defined by CD14 and CD16 or by CD163 expression also varied among individuals. FCM examinations showed that all the monocyte‐associated molecules that were examined varied in expression in this increasing order—CD244, CD4, CD38, CD91, CD11b, toll‐like receptor 2 (TLR2), TIA‐1, CD14 (on CD14Br+ cells), CD86, CD80, HLA‐DQ, CD33, and HLA‐DR. Conclusions Human blood monocytes are heterogeneous among healthy adults with respect to cell counts, subsets, and the levels of expression of monocyte‐associated molecules. An increase in the "non‐classical" (CD14Lo/Neg/CD16+) monocyte subset or in the expression of CD11b or TLR2 have known diagnostic/prognostic implications. CD244 and CD4 have well‐defined functions on lymphocytes but perform unknown activities on monocytes although their expression appears more narrowly controlled. Together, these data suggest that monocytes should be more extensively examined in both clinical and basic contexts. © 2013 International Clinical Cytometry Society